Building Innovative Climate Communication Through The Board Game “Jagad” - Filashofia, Etika; Ridwan, Muhammad; Jalaluddin Usman, Muhammad (UIN Sunan Gunung Djati Bandung, 2025)
Climate change is a critical issue that requires awareness and active participation from all levels of society. However, scientific information about climate change is often difficult to understand and lacks appeal to the general public. This study aims to establish effective climate communication through the development of an educational board game called Jagad. Jagad presents a dynamic conflict between two opposing sides: the “destroyer,” representing human activities that contribute to carbon emissions, and the “savior,” representing mitigation and adaptation efforts to address climate change. The game was developed using a Research and Development (R&D) approach with the ADDIE model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. During the design and development stages, the game mechanics, rule system, and visual elements were constructed through iterative prototyping and playtesting. The validation process involved climate education experts, instructional media specialists, and groups of players from both student and general community backgrounds. The validation results indicated that Jagad received positive responses and was deemed suitable for use as an educational medium. The playtesting showed that the game effectively improved players’ understanding of climate change issues and enhanced their awareness of the importance of mitigation and adaptation actions. These findings demonstrate that Jagad serves as an effective, interactive, and enjoyable learning medium for communicating complex climate issues in an accessible and meaningful way. This game-based approach has the potential to become an inclusive and impactful strategy for climate communication that fosters public awareness and engagement.